Experiments and Fragility Analyses of Piping Systems Connected by Grooved Fit Joints With Large Deformability - Wang, Tao; Shang, Qingxue; Chen, Xi; Li, Jichao (Frontiers in Built Environment, 2019)
The pipes with diameter of 150mm, also called DN150, are often connected by grooved fit joints and employed as the stem pipelines, which are used to transport water vertically to different building stories and distribute it horizontally to different rooms. A large deformability is often required for the grooved fit joints to accommodate the deformation concentrated between adjacent stories during an earthquake. To this end, the grooved fit joint is often improved with a wider groove to achieve such a large deformability. However, its seismic performance has not been thoroughly studied yet. This study conducted quasi-static tests on twelve DN150 grooved fit joints, including four elbow joints and eight DN150-DN80 Tee joints. The mechanical behavior, rotational capacity and failure mode were examined and discussed. The test results indicate that the fracture of the grooved fitting and the pull-out of pipes from the grooved fitting are the major damage patterns at deformations larger than 0.1rad. At small deformations less than 0.06 rad, although slight abrasion and wear were observed on the contact surface between the galvanized steel pipe and the grooved fitting, they would not result in significant leakage. Three damage states are defined accordingly and the fragility models are developed for different grooved fit joints based on test results. Finally, seismic fragility analysis of DN150 stem pipeline system in a 10-story building was conducted. It is demonstrated that the improved joints survive under the maximum credible earthquake and the leakage is highly unlikely to occur.